Speech by Dr. Jamleck Muturi Representing Governor of Embu County on Book Donation Day at Embu University College - Muturi, Jamleck (Embu University College, 2016)
Speech made on behalf of His Excellency Hon. Martin Wambora, Governer Embu County during book donation Ceremony at Embu University College on 24th May 2016 at the Dining Hall.